Kajian Hukum Tindak Pidana Kejahatan Terhadap Kesusilaan Ditinjau Dari UU No 21 Tahun 2007 - Asdi Syukur Dalimunthe; Taufik Siregar; Rizkan Zulyadi (Universitas Medan Area, 2021)
Criminal action is a basic part of an error committed against someone in committing a crime. So for the existence of an error in the relationship between the situation and the actions that cause reproach, it must be in the form of deliberate action or starvation. The purpose of this research is to find out the form of legal protection for victims of decency based on law number 21 of 2007 and to find out how the law is applied to perpetrators of decency crime based on law number 21 of 2007. The type of research in this journal is juridical normative and The nature of the research that I take is descriptive analysis. The form of legal protection for victims of decency based on law number 21 of 2007 is to punish perpetrators of immoral crimes against children with severe criminal sanctions so that the purpose of punishment can be achieved based on the provisions of the Law on the application of the law against perpetrators of criminal acts decency based on law number 21 of 2007 is sentenced to imprisonment for 3 (three) years and a fine of at least Rp. 120,000,000 (one hundred and twenty million rupiah).